Density and Dichotomous Family History Measures of Alcohol Use Disorder as Predictors of Behavioral and Neural Phenotypes: A Comparative Study Across Gender and Race/Ethnicity. (18th February 2020) - Pandey, Gayathri; Seay, Michael J.; Meyers, Jacquelyn L.; Chorlian, David B.; Pandey, Ashwini K.; Kamarajan, Chella; Ehrenberg, Morton; Pitti, Daniel; Kinreich, Sivan; Subbie‐Saenz de Viteri, Stacey; Acion, Laura; Anokhin, Andrey; et al.
Abstract : Background: Family history (FH) is an important risk factor for the development of alcohol use disorder (AUD). A variety of dichotomous and density measures of FH have been used to predict alcohol outcomes; yet, a systematic comparison of these FH measures is lacking. We compared 4 density and 4 commonly used dichotomous FH measures and examined variations by gender and race/ethnicity in their associations with age of onset of regular drinking, parietal P3 amplitude to visual target, and likelihood of developing AUD. Methods: Data from the Collaborative Study on the Genetics of Alcoholism (COGA) were utilized to compute the density and dichotomous measures. Only subjects and their family members with DSM‐5 AUD diagnostic information obtained through direct interviews using the Semi‐Structured Assessment for the Genetics of Alcoholism (SSAGA) were included in the study. Area under receiver operating characteristic curves were used to compare the diagnostic accuracy of FH measures at classifying DSM‐5 AUD diagnosis. Logistic and linear regression models were used to examine associations of FH measures with alcohol outcomes. Results: Density measures had greater diagnostic accuracy at classifying AUD diagnosis, whereas dichotomous measures presented diagnostic accuracy closer to random chance. Both dichotomous and density measures were significantly associated with likelihood of AUD, early onset of regular drinking, and low parietal P3 amplitude, but density measures presented consistently more robust associations. Further, variations in these associations were observed such that among males (vs. females) and Whites (vs. Blacks), associations of alcohol outcomes with density (vs. dichotomous) measures were greater in magnitude. Conclusions: Density (vs. dichotomous) measures seem to present more robust associations with alcohol outcomes. However, associations of dichotomous and density FH measures with different alcohol outcomes (behavioral vs. neural) varied across gender and race/ethnicity. These findings have great applicability for alcohol research examining FH of AUD. Abstract : Using Collaborative Study on the Genetics of Alcoholism (COGA) data, we compared the predictability of four density and four dichotomous family history measures on three outcomes: age of onset of regular drinking, visual P3 amplitude, and likelihood of developing alcohol use disorder (AUD) across gender and race/ethnicity. Density measures had greater diagnostic accuracy at classifying AUD. Both measures significantly predicted all three outcomes, but density measures were more robust among males (vs. females) and Whites (vs. Blacks) for all outcomes.